Knowledge and Prevalence of Emergency Contraceptive Pills among the General Population Visiting a Tertiary Care Centre - Bist, Aayush; Jha, Rajshree; Singh, Meeta; Devkota, Kanchan; Das, Divya; Das, Neha (Journal of Nepalgunj Medical College, 2022)
Introduction: Emergency contraception is a contraceptive method used to prevent unwanted pregnancy in the first few days after unprotected sexual intercourse or contraceptive failure/accident. Many women are unaware of the existence of emergency contraception, misunderstand its use and safety, or do not use it when needed. Especially, residents of the rural regions of Nepal are deprived of family planning services and measures, which cover a major percent of our hospital patients.Aims: To assess the knowledge regarding emergency contraceptive pills, family planning and their prevalence.Methods: A descriptive cross-sectional study with a population size of 392 was performed at Nepalgunj medical college teaching hospital, Kohalpur, starting from January to April 2022. A pre-tested questionnaire containing structural, semi-structural, and open-ended questions in printed form was made as a data collection tool. All the people in this study were interviewed after receiving their consent.Results: 363 out of 392(92.6%) people in our study have known about contraceptives. Only 74.93% responded to having used some sort of contraceptive measure. Oral contraceptive pills were found to be the most used measure in 265 (73%). 222(61.6%) of 363 have heard about emergency contraceptive pills but only 71(31.98%) of them have ever used them. Out of 222 respondents who were aware of emergency contraceptive pills, only 129(58.10%)correctly identified 72 hours as the time limit for the methods to be used. Nineteen respondents (8.56%) believed that emergency contraceptive pills could be used as regular pills. None of them were aware of the use of the intrauterine contraceptive device as an emergency contraception.Conclusion: Despite having knowledge, only two-third population was found using any of the contraceptive measures. Among those having knowledge about emergency contraceptive pills, more than a half people preferred emergency contraceptive pills for any unplanned event. Emergency contraception awareness is essential to prevent unwanted pregnancy.